ANALISA TEORI TRANSCULTURAL NURSING MADELEINE LEININGER - Khoiriyah; Irna Nursanti (Yayasan Nusantara Hasana Berdikari, 2024)
The background to the creation of Leininger's theory, through observations when she worked as a nurse, she identified that there was still a lack of knowledge about culture and care as components needed when caring for patients. Patient care is intended to support compliance, healing, and health which led him to develop the Transcultural Nursing theory. Transcultural Nursing is also known as Culture Care Theory. Nursing theory became a major theme in the last century, and continues today to increase the growth and expansion of professional and phenomenal nursing literature and education. In the early twentieth century, nursing was not recognized as an academic discipline or profession. The achievements of the past century have led to the recognition of nursing in both disciplines and professions. The terms discipline and profession are related, and in some cases can even be used interchangeably, but they are not the same. Nursing theoretical works represent the most comprehensive presentation of systematic nursing knowledge. Therefore, nursing theoretical work is important for the future of the discipline and profession of nursing. This conceptual model comes from the fields of anthropology and nursing. Leininger defines transcultural nursing as a major area of ​​nursing that focuses on the comparative study and analysis of various cultures and subcultures throughout the world by considering values, beliefs, health and illness, and habit patterns. The aim of this theory is to find various ways of caring for clients and universal relations between worldview, social structure, other dimensions, then find a path that is appropriate for different people with the aim of maintaining health, or facing death with a cultural approach.